'Of course we do': inequality, the family and the spell of social mobility - Gideon Calder (Soundings: a journal of politics and culture, 2016)
Social mobility has been announced as a goal by most recent incoming prime ministers, including Theresa May, whose espousal of grammar schools is supposed to promote mobility. Social immobility – sometimes known as ‘class fate’ – is indeed a problem, but nothing will change until there is a recognition that inequality of outcome is a problem in itself, and that tackling intergenerational inequality means doing something about the handing on of family privilege. Current orthodoxies – common sense – about equality and the family are a hindrance to this recognition. Particularly through education, those in a position to give advantages to their children will almost always do so, and this reproduces privilege across the generations. Given unequal life chances and an unequal society, privilege and power will continue to flow through the family and into the next generation.